Investigations on co-gasification and combustion characteristics of coal biomass blend as an alternative transport fuel for tri-cycles - Benson Kariuki; Paul Njogu; Joseph Kamau; Robert Kinyua; Reiner Malessa; Sameer Bachani (Journal of Emerging Science and Engineering, 2024)
Kenya discovered huge deposit of lignite-coal, better utilized through co-gasification to produce syngas, a clean and environmental friendly fuel, with easier application in engines. Blends of Mui-basin coal (MBC), Prosporis juliflora(PJ), Hyphanae compressa(HC) and rice husk(RH) were co-fired with resultant upgraded-syngas operating tricycle engine. Analyzed upgraded-syngas reported improved yields on combustible gases and Hydrogen/Carbon-monoxide ratio (low rank to moderate). Calorific values reported 3.2-11.2% increase. At half-load and relative to neat diesel (ND), peak-pressure improved by 31.6%(MBC-PJ), 24.0%(MBC-HC) and 14.6%(MBC-RH). Additionally, peak-pressure increases as load increases and shifts to the right of top-dead-centre with reported increase of 13.1%MBC-PJ, 15.4%MBC-HC, 18.3 % MBC-RH and 16.5 % for ND. Moreover, Net heat release rate (NHRR) in J/degree increased rapidly at 15-25oafter/TDC for all loads and also increased as the load increased with values of 33.4(HC), 26.8(ND), 28.8(RH) and 37.8(PJ) at no load and 35(HC), 27.8(ND), 30(RH), and 38.9(PJ) at full load condition. The optimal approach for sustainably utilization of MBC is through the novel fuel, in which MBC-PJ ranks the best followed by MBC-HC and lastly MBC-RH.